2000
DOI: 10.2169/internalmedicine.39.794
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Systemic Corticosteroids in the Treatment of Asthma Exacerbation. A Randomized Study.

Abstract: Objective To determine an appropriate duration for a short course of oral steroids in cases of asthmaexacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 5 publications
0
35
0
2
Order By: Relevance
“…An oral glucocorticosteroid dose of 1 mg?kg -1 daily is adequate for treatment of exacerbations in children with mild persistent asthma [355]. A 7-day course in adults has been found to be as effective as a 14-day course [356], and a course of duration 3-5 days is usually considered appropriate in children (Evidence B). Current evidence suggests that there is no benefit in tapering the dose of oral glucocorticosteroids, either in the short term [357] or over several weeks (Evidence B) [358].…”
Section: Initial Assessmentmentioning
confidence: 99%
“…An oral glucocorticosteroid dose of 1 mg?kg -1 daily is adequate for treatment of exacerbations in children with mild persistent asthma [355]. A 7-day course in adults has been found to be as effective as a 14-day course [356], and a course of duration 3-5 days is usually considered appropriate in children (Evidence B). Current evidence suggests that there is no benefit in tapering the dose of oral glucocorticosteroids, either in the short term [357] or over several weeks (Evidence B) [358].…”
Section: Initial Assessmentmentioning
confidence: 99%
“…[28,29] • CS need to be continued for 7 -14 days. [30] • CS have been shown to be effective when administered by MDI or nebulisation in acute asthma, [31,32] but the inhaled route is not costeffective or as reliable as systemic administration in acute asthma. There is insufficient evidence that the inhaled route can replace systemic CS in acute asthma.…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
“…Two placebo-controlled studies have examined duration of OCS treatment in patients discharged from hospital or ED. HASEGAWA et al [9] found no difference between 1 and 2 weeks of oral prednisolone 0.5 mg?kg -1 , given after 3 days' i.v. corticosteroids, but JONES et al [10] found that symptoms were higher in patients treated with prednisolone (40 mg) for 5 days compared with 10 days.…”
Section: Duration Of Ocs Therapymentioning
confidence: 96%